The impact of prophylactic dexamethasone on nausea and vomiting after thyroidectomy: a systematic review and meta-analysis. - Zhenhong Zou; Yuming Jiang; Mingjia Xiao; Ruiyao Zhou (PLoS ONE, 2014)
BACKGROUND: We carried out a systematic review and meta-analysis to evaluate the impact of prophylactic dexamethasone on post-operative nausea and vomiting (PONV), post-operative pain, and complications in patients undergoing thyroidectomy. METHODS: We searched Pubmed, Embase, and Cochrane Library databases for randomized controlled trials (RCTs) that evaluated the prophylactic effect of dexamethasone versus placebo with or without other antiemetics for PONV in patients undergoing thyroidectomy. Meta-analyses were performed using RevMan 5.0 software. RESULTS: Thirteen RCTs that considered high quality evidence including 2,180 patients were analyzed. The meta-analysis demonstrated a significant decrease in the incidence of PONV (RR 0.52, 95% CI 0.43 to 0.63, P < 0.00001), the need for rescue anti-emetics (RR 0.42, 95% CI 0.30 to 0.57, P<0.00001), post-operative pain scores (WMD -1.17, 95% CI -1.91 to -0.44, P = 0.002), and the need for rescue analgesics (RR 0.65, 95% CI 0.50-0.83, P = 0.0008) in patients receiving dexamethasone compared to placebo, with or without concomitant antiemetics. Dexamethasone 8-10mg had a significantly greater effect for reducing the incidence of PONV than dexamethasone 1.25-5mg. Dexamethasone was as effective as other anti-emetics for reducing PONV (RR 1.25, 95% CI 0.86-1.81, P = 0.24). A significantly higher level of blood glucose during the immediate post-operative period in patients receiving dexamethasone compared to controls was the only adverse event. CONCLUSIONS: Prophylactic dexamethasone 8-10mg administered intravenously before induction of anesthesia should be recommended as a safe and effective strategy for reducing the incidence of PONV, the need for rescue anti-emetics, post-operative pain, and the need for rescue analgesia in thyroidectomy patients, except those that are pregnant, have diabetes mellitus, hyperglycemia, or contraindications for dexamethasone. More high quality trials are warranted to define the benefits and risks of prophylactic dexamethasone in potential patients with a high risk for PONV.